Delamination of organic coating on carbon steel studied by scanning Kelvin probe force microscopy - Pan, Tongyan (Surface and interface analysis, 2013)
Corrosion‐induced delamination of an epoxy coating on the AISI/SAE 1045 carbon steel was studied under a humid atmospheric condition (temperature of 25 °C, 1 standard atmospheric pressure, relative humidity of 90%) by the technique of scanning Kelvin probe force microscopy (SKPFM). Surface‐polished 1045 samples were first cold‐coated with the epoxy and then subject to the atmospheric corrosion under the specified condition. At predetermined time intervals, surface Volta potential differences of the samples were measured using the SKPFM over the dry surface of epoxy coating. The map of Volta potential differences demonstrated high contrasts among three characteristic zones: intact steel‐epoxy interface, delaminated interface, and interface with active corrosion, which was then linked to the actual corrosion potential of the steel (measured using a potentiostat with respect to a saturated calomel electrode) based on a rigorous calibration procedure. It was found that the SKPFM was able to provide direct and nondestructive detection of early active corrosion and coating delamination on steels at a submicroscopic resolution, which outperformed the conventional electrochemical techniques for the same purposes. Copyright © 2012 John Wiley & Sons, Ltd.